Inflation Dynamics and Local Political Responses in Local Political Stability: A Comparative Study of Malaysia, and Indonesia and Turkey in 2020-2025 - Iskandar, Eddy; Samsurijan, Mohamad Shaharudin; Pratama, Prawira Yudha (Jurnal Studi Pemerintahan, 2025)
This study examines the relationship between inflation dynamics, economic policy responses, and local political stability in three countries with differing institutional contexts, Turkey, Malaysia, and Indonesia, over the period 2020– 2025. The research is grounded in a comparative descriptive-analytic ap- proach, enabling a systematic assessment of how inflationary pressures in- teract with political and institutional arrangements at the sub-national level. Methodologically, the study utilizes official macroeconomic statistics comple- mented by secondary sources, including economic policy reports, working papers, and peer-reviewed literature produced by international institutions such as the IMF, World Bank, and OECD. The Qualitative analysis is further supported by NVivo 14, which is used to examine policy discourse patterns and visualize comparative trends across countries. The findings demonstrate that inflation extends beyond its conventional role as a macroeconomic vari- able and exerts a direct influence on socio-political dynamics and local politi- cal stability. Turkey exhibits pronounced inflation volatility driven by uncon- ventional monetary policies under strong political influence, which has inten- sified social tensions and weakened local stability. In contrast, Malaysia has maintained relatively moderate inflation through prudent monetary manage- ment and targeted subsidy policies, supporting social stability despite changes in national leadership. Indonesia represents an intermediate case, where co- ordinated monetary and fiscal interventions are deployed to contain inflation and sustain social resilience amid an ongoing political transition. It addresses a critical gap in existing research on economic pressures and socio-political resilience at the sub-national level.